Respon Pemupukan terhadap Hasil dan Kualitas Buah Jambu Biji Kristal (Psidium guajava L. cv. Kristal) - SUAMBA, I WAYAN; RAI, I NYOMAN; WIJANA, GEDE (Agrotrop : Journal on Agriculture Science, 2018)
Response of Fertilization on Yield and Quality of Guava (Psidium guajava L. cv. “Kristal”). Grower of “Kristal” guava (Psidium guajava L. cv Kristal) in Bali have not adopted good agriculture pratices (GAP) yet. Hence, it’s yield and quality has been low. The purpose of this study was to evaluate yield and quality of “Kristal” guava in response to fertilization. The experiments was arranged in Randomized Block Design (RBD) with eighteen replications. The treatments were P0 (organic fertilizer 5 kg), P1 (organic fertilizer 5 kg, Urea 250 g, TSP 300 g, KCl 300 g, and Gypsum 500 g) and P2 (organic fertilizer 5 kg, Urea 250 g, TSP 300 g, KCl 300 g, and Gypsum 500 g /plant, Zn and Cu (0,4%)). The result indicated that the maximum fruit weight per plant (15,22 kg) and fruit number per plant (55,56 fruit) were found on fertilizer with organic fertilizer 5 kg, Urea 250 g, TSP 300 g, KCl 300 g, and Gypsum 500 g , Zn and Cu (0,4%) (P2). The maximum fruit diameter (8,27 cm) and fruit weight per fruit (273,55 g) were also found on fertilizer with organic fertilizer 5 kg, Urea 250 g, TSP 300 g, KCl 300 g, and Gypsum 500 g , Zn and Cu (0,4%).